PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP SIKAP TOLERANSI PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS V DI UPT SPF SD INPRES BARAYA 1 - Putri Ratna; Rismawati; Tri Gustaf (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the role playing learning model on the tolerance attitude of fifth grade students in the Pancasila Education subject at the UPT SPF SD Inpres Baraya 1. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research sample consisted of 23 students. Data collection techniques used questionnaires and observations. Data analysis used descriptive and inferential statistics through the Shapiro-Wilk normality test and the Wilcoxon hypothesis test. The results showed an average pretest score of 19.70 and an average posttest score of 29.35. A significance value of 0.001 <0.05 indicates that there is a significant influence of the role playing learning model on students' tolerance attitudes.